PERCENTAGE YIELD OF VOLATILE OIL FROM WOOD DUST OF TREES FROM SAW MILL IN HIMALAYAN AREAS - Vashist, Hemraj; Sharma, Diksha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Trees with medicinal values have always been ignored and neglected from their inherent medicinal value. Instead of their medicinal use, such plants are widely used by carpenters and also by people for cooking. The irrational uses of such valuable flora are diminishing our medicinal plants' bank. There is no doubt that the uses of such plants by carpenters are a necessity of growing society. Then, we need to opt any other middle way to fulfill both the necessities from such valuable flora. By considering this, all the present study is focused on the extraction of volatile oil from sawdust of Pinus roxburghii and Cedrela toona (SDPR and SDCT) was carried out in the present study. Methods: Here, in the present work, we have collected the fresh powder near from the running saw of working carpenter cutting Pinus roxburghii wood and Cedrela toona wood into flat board. The SDPR and SDCT were then weighed and filled separately to two 500 ml round bottom flask, and clevenger apparatus assemblies were adjusted for both. The temperature was adjusted at75Â°C. Hydrodistillation was continued for 3 hrs. Result: The result revealed 0.5% v/w of volatile oil from SDPR in 3 hrs. The meniscus observed for SDCT is slightly blurred up to 0.5 ml (2 mm) which was considered as volatile oil. The total percentage so obtained was calculated as 0.25% v/w. Conclusion: The present study may guide to utilize the saw rust from pine and red cedar plant to isolate valuable medicinal constituents. Further, the study may help the researcher to use wood dust to research different ways. Keywords: Pinus roxburghii, Cedrela toona, Hydrodistillation, Herbal medicine.